Environmental Stresses and Your Florida Lawn - Laurie E. Trenholm (EDIS, 2008)
Revised! ENH-153, a 3-page fact sheet by L. E. Trenholm, is part of the Florida Lawn Handbook. It provides homeowners with tips to maintain a stress-resistant lawn by ensuring sufficient stores of carbohydrates, achieve maximum root growth, and supply appropriate nutrients. Includes references throughout. Published by the UF Department of Environmental Horticulture, August 2008.